Komunikasi Injil Lintas Budaya Mengenai Roh Kudus dalam Tradisi Ari-ari pada Masyarakat Jawa di Surakarta - Lukmono, Irawan Budi; Nelwan, Richard Leonardo Arnic (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
The aim of this research is to find the communication of the gospel regarding the Holy Spirit in the ari-ari tradition in Javanese society. This research uses a qualitative approach with phenomenological methods. In this research, the data aggregation technique used by researchers is a literature study or written document review. The result of this research is the communication of the gospel regarding the Holy Spirit (local pneumatology) in the ari-ari tradition in the Javanese community in Surakarta.